TOWARDS A WORLD MORALITY - Chethimattam, J.B. (Journal of Dharma, 1991)
Brlhadaranyaka Upanishad, a classical work of Indian antiquity, composed almost at the same time as the Republic of Plato, explains the emergence of Dharma or Moral Law as necessitated by the rise of different social classes: In the beginning this world was Atman alone in the form of a person. Feeling the need to get out of his loneliness he created the different classes of people. But to keep the harmony among the classes, to control even the Kshatriyas, the fierce class of rulers, he created Dharma. "